2001
DOI: 10.1016/s0005-2736(01)00330-3
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption to polyethylene glycol modified liposomes from fibrinogen solution and from plasma

Abstract: Unmodified and polyethylene glycol (PEG) modified neutral and negatively charged liposomes were prepared by freeze-thaw and extrusion followed by chromatographic purification. The effects of PEG molecular weight (PEG 550, 2000, 5000), PEG loading (0-15 mol%), and liposome surface charge on fibrinogen adsorption were quantified using radiolabeling techniques. All adsorption isotherms increased monotonically over the concentration range 0-3 mg/ml and adsorption levels were low. Negatively charged liposomes adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(93 citation statements)
references
References 41 publications
5
88
0
Order By: Relevance
“…However, the lipid membranes can endure the diluted serum. There are almost no signal changes for membranes after treating with 10% serum (data not shown), which is in accordance with the results in published papers [32,33]. As a result, it is proposed that the lipid membrane soluble effect of serum is a function of concentration.…”
Section: Stability In Serumsupporting
confidence: 89%
“…However, the lipid membranes can endure the diluted serum. There are almost no signal changes for membranes after treating with 10% serum (data not shown), which is in accordance with the results in published papers [32,33]. As a result, it is proposed that the lipid membrane soluble effect of serum is a function of concentration.…”
Section: Stability In Serumsupporting
confidence: 89%
“…9,10) In another report, it was indicated that PEG-modification of negatively charged liposomes can inhibit the binding of fibrinogen to liposomes, but there were no effects of PEG on nearly neutral liposomes (PC : PG : PE : Chol= 69 : 4 : 4 : 23). 11) Negatively charged liposomes have often been used to show the inhibition of protein adsorption by PEG as described above, but the effect of PEG on nearly neutral or slightly negatively-charged liposomes remains unclear.…”
mentioning
confidence: 99%
“…2). Since positively or negatively charged particles strongly interact with serum proteins and biomolecules, 20,21) a neutral surface is desirable for in vivo application. Collectively, 5 mol% of STR-R8 seemed to be the optimal density.…”
Section: Resultsmentioning
confidence: 99%